Investigating variation the effects of social organization and social setting - Dorian, Nancy C. (New York ; Oxford : Oxford University Press, 2009)
Linguistic variation has mostly been studied in communities that conform to certain forms of social organization. This book explores variation in small enclaves of non-dominant languages such a fishing communities in Gaelic speaking Scotland.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Scottish Gaelic language -- Dialects -- Scotland -- Sutherland; Scottish Gaelic language -- Variation; Scottish Gaelic language -- Social aspects; Fishers -- Scotland -- Sutherland -- Language